Co-Inoculation of Mesorhizobium ciceri with Either Bacillus sp. or Enterobacter aerogenes on Chickpea Improves Growth and Productivity in Phosphate-Deficient Soils in Dry Areas of a Mediterranean Region - Imane Benjelloun; Imane Thami Alami; Mohamed El Khadir; Allal Douira; Sripada M. Udupa (Plants, 2021)
Biological nitrogen fixation requires a large amount of phosphorus (P). However, most of the soils are P-deficient and the extensive use of P- chemical fertilizers constitute a serious threat to the environment. In this context, two field experiments were carried out to investigate the effect of co-inoculation of Mesorhizobium ciceri with phosphate solubilizing bacteria (PSB), Bacillus sp., and Enterobacter aerogenes, on chickpea as an alternative to chemical nitrogen (N) and phosphorous fertilizers in P-deficient soils in dry areas of Morocco. The results revealed that combined inoculation of chickpea with rhizobia and PSB showed a significant enhancement of chickpea nodulation, biomass production, yields and N, P, and protein content in grains as compared to single inoculation or single application of N or P. A significantly higher increase was obtained by inoculating chickpea with Mesorhizobium sp. MA72 combined with E. aerogenes P1S6. This combination allowed an enhancement of more than 270% in nodulation, 192% in shoot dry weight and 242% in grain yield. The effect of this combination was equivalent to the effect of combined application of N and P fertilizers. Formulation of biofertilizers based on tasted strains could be used for chickpea co-inoculation in P-deficient soils for an eco-friendly sustainable production of chickpea.